Comparison of Trendelenburg Tilt Angles 0°, 10°, and 25° on The Diameter of The Internal Jugular Vein And Optical Nerve Sheath - Rais, Rahman; Tavianto, Doddy; Aditya, Ricky; Galuh, Harry (Jurnal Anestesi Perioperatif, 2026)
Introduction: The trendelenburg position is widely utilized to facilitate central venous cannulation. However, the optimal angle to balance efficacy and safety remains debated.Methods: This experimental study aimed to compare the impact of 0°, 10°, and 25° trendelenburg tilt angles on internal jugular vein (IJV) and optic nerve sheath (ONS) diameters in 28 healthy adults. Measurements of maximal diameters were performed using ultrasound at each specified angle from May to June 2024.Results: Results demonstrated that while both 10° and 25° positions significantly increased IJV and ONS diameters compared to 0° (P<0.05), the 25° tilt caused ONS diameters to exceed the critical safety threshold (>4.5 mm) in five subjects. In contrast, the 10° position achieved a significant increase in IJV diameter while successfully maintaining ONS measurements within safe limits.Discussion: The findings suggest that although greater trendelenburg angles enhance IJV dilation, they may also increase ONS diameter beyond safe thresholds, raising the risk of elevated intracranial pressure. Therefore, balancing vascular access benefits with neurological safety is essential when determining the appropriate tilt angle.Conclusion: A 10° trendelenburg tilt is recommended as the optimal angle to increase IJV diameter without elevating ONS diameter in healthy populations.